Exploring Children’s Social and Emotional Representations of the COVID-19 Pandemic - Idoiaga, Nahia; Berasategi, Naiara; Eiguren, Amaia; Picaza, Maitane (Frontiers in Psychology, 2020)
COVID-19, a new Emerging Infectious Disease (EID), has spread throughout the world, including Europe. Spain, in particular, has witnessed a significant outbreak of the pandemic. All classes have been cancelled and the Government have declared a state of emergency, ordering the lockdown and confinement of the entire population. All children in the country have been confined to their homes since March 13 and are not allowed to leave at any time. This population is thus facing the harshest restrictions. Given the vulnerable situation of children, the aim of this research is to understand how they represent and emotionally cope with the COVID-19 crisis. A free association exercise elicited by the word “coronavirus” was completed by 228 children (age range: 3-12 years) from the North of Spain. To analyse the content, we employed the Reinert method with Iramuteq software for lexical analysis. The results revealed that children represent the COVID-19 as an enemy that is being fought by the doctors. Children are afraid and worried about catching the virus, but mainly because they think they can infect their grandparents, and this makes them feel guilty. Moreover, the lockdown situation has produced conflicting emotions in the children. On the one hand, they are scared, nervous, lonely, sad, bored and angry, but they also feel safe, calm and happy with their families. These results indicate the need for Governments to also consider children in their management of the current situation by placing greater emphasis on social and inclusive policies to help alleviate the possible effects that they may suffer as a consequence of the pandemic and the lockdown. In short, there is a need to address the psychological, educational, social, health, and wellbeing needs of children.